Assessments of the Sister City Partnership between Baubau, Indonesia and Seoul, South Korea - Susiatiningsih, Rr. Hermini; Alfian, Muhammad Faizal; Setiyaningsih, Dewi (Global Strategis, 2026)
This study examines the sister city partnership between Baubau, Indonesia, and Seoul, South Korea, with a focus on evaluating its alignment across cultural, educational, economic, and governance dimensions. The partnership was founded in 2009 with the goal of adopting Hangeul, Korea's phonetic writing system, to preserve the endangered Ciacia language. Although there are no historical or genealogical connections between the two cities, the partnership is the result of a calculated effort that has produced significant cultural and educational results. Through interviews with key stakeholders, document analysis, and field observations, the study employs six evaluative indicators ranging from cultural influence to community engagement to assess the partnership's impact. The resulting compatibility score of 17 indicates a moderate alignment, highlighting strengths in cultural revitalization and grassroots participation. However, the study identifies imbalances in cultural exchange and limited economic cooperation, suggesting a risk of cultural asymmetry and underutilized development potential. This paper provides the contention that though the partnership is a prime example of soft power diplomacy, it also requires evaluated approaches for ensuring equal representation and its continued viability. The results highlight how crucial reciprocal participation and contextual awareness are to subnational international cooperation, especially when working with groups that have different linguistic and cultural identities. Keywords: Sister City, Baubau-Seoul Cooperation, Cultural Diplomacy, Subnational in International Relations Penelitian ini mengkaji kemitraan sister city antara Baubau, Indonesia, dan Seoul, Korea Selatan, dengan fokus pada evaluasi kesesuaiannya dalam dimensi budaya, pendidikan, ekonomi, dan tata kelola. Kemitraan ini didirikan pada tahun 2009 dengan tujuan mengadopsi Hangeul, sistem penulisan fonetik Korea, untuk melestarikan bahasa Ciacia yang terancam punah. Meskipun tidak terdapat hubungan historis atau genealogi antara kedua kota, kemitraan ini merupakan hasil dari upaya strategis yang menghasilkan dampak signifikan dalam bidang budaya dan pendidikan. Melalui wawancara dengan para pemangku kepentingan utama, analisis dokumen, dan observasi lapangan, studi ini menggunakan enam indikator evaluatif, mulai dari pengaruh budaya hingga partisipasi komunitas, untuk menilai dampak dari kemitraan ini. Skor kompatibilitas sebesar 17 menunjukkan keselarasan yang moderat, dengan kekuatan pada revitalisasi budaya dan keterlibatan akar rumput. Namun, studi ini juga menemukan ketidakseimbangan dalam pertukaran budaya serta keterbatasan kerja sama ekonomi, yang mengindikasikan potensi risiko asimetri budaya dan peluang pembangunan yang belum dimaksimalkan. Artikel ini berargumen bahwa meskipun kemitraan ini mencerminkan praktik diplomasi soft power, dibutuhkan strategi yang dikalibrasi ulang untuk menjamin representasi yang adil dan keberlanjutan jangka panjang. Temuan ini menekankan pentingnya sensitivitas kontekstual dan keterlibatan timbal balik dalam kerja sama internasional subnasional, terutama ketika melibatkan komunitas dengan identitas linguistik dan budaya yang khas. Kata-kata Kunci: Sister City, Kerjasama Baubau-Seoul, Diplomasi Budaya, Kerja sama Hubungan Internasional Subnasional